2021
DOI: 10.1016/j.ijscr.2021.106368
|View full text |Cite
|
Sign up to set email alerts
|

Achilles' tendon rupture dancing the ‘Jerusalema’ – A case series

Abstract: Introduction and importance The weekend warrior has long been prey to musculoskeletal injuries as a result of intermittent, high intensity activity. The Achilles tendon is known to be particularly vulnerable in this population cohort but during the COVID-19 lockdowns in Ireland and all over the world there has been a certain level of detraining and deconditioning among all age groups and populations. Throughout the worldwide restrictions, viral internet challenges and dances have enca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This is especially true pertaining to AATR injuries, which are particularly prone to disuse, atrophy, and tendinosis [ 15 , 20 ]. Roopnarinesingh et al published a small case series of three patients who sustained AATRs over a ten-day period in 2021, all due to the ‘Jerusalema’ dance, and highlighted the importance of precautions when returning from COVID induced lack of physical activity to deceptively demanding physical activity [ 27 ]. An investigation by Baker et al demonstrated that NFL injuries spiked significantly in the first four weeks of the 2020–2021 regular season after the 2020 preseason was canceled due to the COVID pandemic [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true pertaining to AATR injuries, which are particularly prone to disuse, atrophy, and tendinosis [ 15 , 20 ]. Roopnarinesingh et al published a small case series of three patients who sustained AATRs over a ten-day period in 2021, all due to the ‘Jerusalema’ dance, and highlighted the importance of precautions when returning from COVID induced lack of physical activity to deceptively demanding physical activity [ 27 ]. An investigation by Baker et al demonstrated that NFL injuries spiked significantly in the first four weeks of the 2020–2021 regular season after the 2020 preseason was canceled due to the COVID pandemic [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tension offloading of the skin following Achilles repair may mitigate mechanopathologic stimulus for scar formation associated with early post-operative mobilization and daily physical therapy range-of-motion exercises. Given the sudden increase in Achilles tendon ruptures since the onset of the COVID pandemic, this case study provides data of this device’s potential therapeutic use to the increasing number of patients undergoing this procedure [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%